Visible‐Light‐Excited Room‐Temperature Phosphorescence in Water by Cucurbit[8]uril‐Mediated Supramolecular Assembly. (3rd January 2020) - Wang, Jie; Huang, Zizhao; Ma, Xiang; Tian, He
Abstract: Solid‐state materials with efficient room‐temperature phosphorescence (RTP) emissions have found widespread applications in materials science, while liquid or solution‐phase pure organic RTP emission systems has been rarely reported, because of the nonradiative decay and quenchers from the liquid medium. Reported here is the first example of visible‐light‐excited pure organic RTP in aqueous solution by using a supramolecular host‐guest assembly strategy. The unique cucurbit[8]uril‐mediated quaternary stacking structure allows tunable photoluminescence and visible‐light excitation, enabling the fabrication of multicolor hydrogels and cell imaging. The present assembly‐induced emission approach, as a proof of concept, contributes to the construction of novel metal‐free RTP systems with tunable photoluminescence in aqueous solution, providing broad opportunities for further applications in biological imaging, detection, optical sensors, and so forth. Abstract : Echte Farben : Aggregationsinduzierte Emission wurde genutzt, um ein einfaches Farbstoffmolekül mit Raumtemperatur‐Phosphoreszenz und abstimmbarer Photolumineszenz in wässriger Lösung zu versehen. Die erhaltene supramolekulare Struktur hat faszinierende photophysikalische Eigenschaften und ermöglicht die Herstellung von mehrfarbigen Hydrogelen sowie die Bildgebung von Zellen.